2009
DOI: 10.1136/bjo.2008.144691
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of postoperative surface light scattering of different intraocular lenses

Abstract: The surface scattering of MA60BM and SA60AT is higher than that of AR40 and ClariFlex. The grades of surface scattering differ among the manufacturers, even with the same acrylic material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 11 publications
0
37
0
Order By: Relevance
“…[4][5][6] We call this phenomenon "whitening." While decreased visual function due to poor transparency of the IOL has been described, including several cases of patients with calcium deposits 7-10 and the occurrence of advanced glistening, [11][12][13][14] few studies suggest an effect of whitening on visual function.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…[4][5][6] We call this phenomenon "whitening." While decreased visual function due to poor transparency of the IOL has been described, including several cases of patients with calcium deposits 7-10 and the occurrence of advanced glistening, [11][12][13][14] few studies suggest an effect of whitening on visual function.…”
Section: Discussionmentioning
confidence: 97%
“…We initially suggested that whitening had only minor effects on visual function, 15 but that severe whitening might decrease visual function. Miyata et al 6 investigated the intensity of surface light scattering in various IOLs over time and reported that surface light scattering intensities in AR40 and ClariFlex IOLs did not change over time, whereas in MA60BM and SA60AT they increased. At around 3 years postoperatively, they found no effects on visual function in any patients with implantation of either the MA60BM or SA60AT lens.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The development of mild PCO is not critical for corrected distance visual acuity (CDVA) with monofocal IOL, whereas the near visual acuity with multifocal IOLs is more sensitive with the development of PCO [10][11][12][13]. Lundqvist et al [14] reported that the cumulative incidence of neodynium:YAG (Nd:YAG) laser capsulotomy due to PCO in the Acrysof monofocal IOL (MA60BM; Alcon Laboratories, Fort Worth, TX) increased markedly between 2.5 and 6 years postoperatively in patients aged \65 years; however with the AcrySof IOL, increased surface light scattering is another concern [8,9]. Although a substantial impact on the CDVA has not been reported with monofocal IOLs, a case with decreased contrast sensitivity has been addressed [7].…”
Section: Introductionmentioning
confidence: 96%
“…In one study on patients with a diffractive multifocal IOL, the bifocality that provides both UDVA and UNVA was maintained for 3 years postoperatively [6]. However, with multifocal IOLs stability over the longer term is more important since the outcome is more affected by postoperative degradation, such as development of posterior capsule opacification (PCO) and surface light scattering [7][8][9]. The development of mild PCO is not critical for corrected distance visual acuity (CDVA) with monofocal IOL, whereas the near visual acuity with multifocal IOLs is more sensitive with the development of PCO [10][11][12][13].…”
Section: Introductionmentioning
confidence: 96%